OBERHOLSTER, P.S. Inventory of documents - OBERHOLSTER, P.S. (ARCA, 2018)
Founder of the National Party Branch in Douglas; Correspondence, circulars and information regarding inter alia the 1924 and other elections; pamphlets; photos
COVERAGE: 0.02 metres
Keywords: OBERHOLSTER, P.S.; Inventories; Politicians; National Party